2018
DOI: 10.29252/ijree.3.3.72
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Using Podcasts on Iranian Autonomous /Non-Autonomous EFL Learners’ Listening Comprehension Ability at Pre-Intermediate Level

Abstract: The aim of the current study was to investigate whether Podcasts would have an effect on Iranian autonomous and non-autonomous EFL learners' listening comprehension ability at pre-intermediate level. For this purpose, 60 Iranian pre-intermediate EFL learners at some Iranian institutes participated in the experiment of the study. Then they were divided into two groups based on an Oxford Placement Test (OPT) and an autonomy questionnaire. The participants of each group were assigned randomly into two experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
0
0
Order By: Relevance
“…Gholami and Mohammadi (2015) argued that podcasting through mobile learning with offline and online services increased students' motivation. Most of the research done has been focused on the development of the listening skill (Abdulrahman et al, 2018;Al Sheef & Althobaiti, 2019;Kay, 2012;Rahman et al, 2018;Salsabila et al, 2021;Sayadi & Heidar, 2018;Şendağ et al, 2018;Shahid & Ali, 2017). Indahsari (2020) showed that students improved their listening skills and motivation toward EFL learning.…”
Section: Previous Researchmentioning
confidence: 99%
“…Gholami and Mohammadi (2015) argued that podcasting through mobile learning with offline and online services increased students' motivation. Most of the research done has been focused on the development of the listening skill (Abdulrahman et al, 2018;Al Sheef & Althobaiti, 2019;Kay, 2012;Rahman et al, 2018;Salsabila et al, 2021;Sayadi & Heidar, 2018;Şendağ et al, 2018;Shahid & Ali, 2017). Indahsari (2020) showed that students improved their listening skills and motivation toward EFL learning.…”
Section: Previous Researchmentioning
confidence: 99%
“…Another advantage of podcasting is that it can improve students' independence in learning. By producing their own podcasts behind the scenes, students can sharpen their public speaking skills while avoiding the potential nervousness of speaking in front of an audience (Sayadi and Mashhadi Heidar, 2018). Because it provides advantages, using a podcast to improve a student's speaking ability can be effective and beneficial.…”
Section: The Significance Of Podcastingmentioning
confidence: 99%
“…Podcast refers to a set of media file which specifically includes audio or video materials (Chan, Chi, & Lin, 2011) and is available on the internet and can be uploaded periodically (M. M. Hasan & Hoon, 2012). As a teaching aid, podcast can be used for prompting students into deep learning, providing a stepping-stone for the learning outcomes (Morrissey, 2012) and extending student' feedback (Scutter, Stupans, Sawyer, & King, 2010). In essence, the variety of podcast content helps the learning process carried out by both students and teachers (Alfa, 2020).…”
Section: Using Podcast For English Language Teachingmentioning
confidence: 99%
“…The existing studies investigating the use of podcast in language teaching could be categorized into four tendencies. First, the effects of podcast on language learning particularly on various language skills such as listening, speaking, reading, and writing (Abdulrahman et al, 2018;Aditya, 2019;Chung & Kim, 2014;Morrissey, 2012;Sayadi & Heidar, 2018;Silmawati & Muslem, AsnSamad, 2018). Second, the utility of podcast for language learning (Alfa, 2020;Indahsari, 2020;Kay, 2012;Lio & Marafat, 2019;Rajic, 2013;Ramli, 2018;Samad, Bustari, & Ahmad, 2017;Yoestara, 2019).…”
Section: Introductionmentioning
confidence: 99%